A Comparison On The Semen Characteristics And Extenders For Freezing Semen Of The Swamp, River And Crossbred Buffalo (Bubalus Bubalis) - P. Ramakrishnan, (1990)

(untitled)
A study was undertaken ( i ) to investigate and compare the effect of chromosome make up on semen characteristics of three buffalo genotypes , viz swamp , 2n=48 ; river 2n=50; and crossbred , 2n=49; ( ii ) to investigate the influence of climate on the semen characteristics of the three genotypes ; (iii) to study the freezability of the semen of the three buffalo genotypes using four different extenders . Theresults showed that in general , the semen quality was better i n the swamp buffalo as compared to the river type. Except for the semen colour, density, volume and spermatozoa concentration , all the other semen characteristics of the crossbred buffalo were inferior to that of the other two genotypes . The lower mean values for mass activity, progressive motility percentage , percent intact acrosome and the higher incidence of total spermatozoa abnormalities in the crossbred buffalo ( 2n=49) semen indicate that the odd number chromosome complement of this genotype has an adverse effect on its semen characteristics.